Simulating the mechanisms of serrated flow in interstitial alloys with atomic resolution over diffusive timescales - Yue Zhao (Nature Portfolio, 2020)
Understanding the plastic deformation mechanism within specific ranges of temperature and strain in metal alloys is of great technological importance. Here the authors report on dynamic simulations of dislocation–solute coevolution in tungsten crystals containing a few atomic parts per million of interstitial oxygen and their relation to unstable plastic flow.